Experimental investigation of a highly efficient, low-cost PVC-Rollers Sandwich (PVC-RS) seismic isolation. (October 2021) - Tsiavos, Anastasios; Sextos, Anastasios; Stavridis, Andreas; Dietz, Matt; Dihoru, Luiza; Alexander, Nicholas A.
Abstract: This paper focuses on the large-scale experimental investigation of a novel, highly efficient, low-cost and easily constructible seismic isolation system, defined as PVC-Rollers Sandwich (PVC-RS) seismic isolation. The proposed system is based on the placement of spherical roller bearings between two PVC surfaces in a sandwich configuration. This configuration triggers a desirable rolling behaviour between the rollers and the PVC surfaces, thus isolating the motion of the structure from the ground excitation. The large-scale shaking table investigation of the seismic response of a scaled-down masonry and a scaled-down steel model of a seismically isolated prototype structure using PVC-RS has unveiled the activation of the rolling behaviour of the structure at a desirably low acceleration amplitude of 0.05g-0.1g. The reliability of this low-acceleration response of the structure was confirmed for ground motion excitations of different amplitudes and frequency characteristics. The experimentally tested variation on the amount, the material and the diameter of the roller bearings allows for the implementation of different design alternatives of the presented system, according to the seismic design requirements and the seismic performance objectives for each location.